2020
DOI: 10.1111/ajag.12788
|View full text |Cite
|
Sign up to set email alerts
|

Fifth‐year medical students' perceptions of the importance of frailty and competence in assessing, diagnosing and managing frailty before and after a geriatric medicine course

Abstract: Objective: To assess the changes in fifth-year medical students' perceptions of the importance of frailty and competence in assessing, diagnosing and managing frailty after a 4.5-week geriatric medicine course. Methods: Students' perceived importance and competence was assessed before and after the course using a 26-item Likert scale questionnaire with scores ranging from 1 to 6. Results: Students' perceptions of the importance of defining frailty (P = .01), explaining what frailty is (P = .03), advising on nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Following title and abstract screening and full‐text review, 10 studies, all published between 2018 to 2021, were included (Figure 1). These studies reported on the effectiveness of nine frailty training programs (Table 2) conducted in five Western countries 19–27 . Quality assessment was moderate with a mean of 5.9/8 for cross‐sectional studies and 8/11 for qualitative studies (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following title and abstract screening and full‐text review, 10 studies, all published between 2018 to 2021, were included (Figure 1). These studies reported on the effectiveness of nine frailty training programs (Table 2) conducted in five Western countries 19–27 . Quality assessment was moderate with a mean of 5.9/8 for cross‐sectional studies and 8/11 for qualitative studies (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The largest program, described by Donoghue et al, was completed by 356 participants, although fewer than half (approximately 40%) were involved in the assessment of the program. Two studies reported on training programs for medical students 19,25 . Three trained Emergency Department staff 22,26,27 and one reported on primary health care professional education 24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations